Boosting alkaline hydrogen evolution and Zn–H2O cell induced by interfacial electron transfer. (May 2020) - Cheng, Fanpeng; Wang, Lin; Wang, Hanqing; Lei, Chaojun; Yang, Bin; Li, Zhongjian; Zhang, Qinghua; Lei, Lecheng; Wang, Shaobin; Hou, Yang
Abstract: Directly use of metal-organic frameworks (MOFs) as electrocatalysts by taking the intrinsic advantages of MOFs architecture for water splitting have attracted tremendous interest. Herein, we reported a vapor-phase transformation method to construct well-aligned nickel based MOFs (Ni-MOF) nanoarrays grown on electrochemical exfoliated graphite (EG) foil and further phosphorization treatment to derive a Ni-MOF/Ni2 P@EG. In such a hybrid structure, Ni2 P with a particle size of ~9 nm was encapsulated into Ni-MOF nanorod arrays on EG foil. Profiting from super hydrophilic nature and nanoarray feature, the Ni-MOF/Ni2 P@EG hybrid displayed an excellent activity of hydrogen evolution reaction (HER) with low overpotentials of 132 and 233 mV at 10 and 150 mA cm −2, respectively, as well as a small Tafel slope of 59 mV dec −1 in alkaline media, which are among the best values in all previously reported MOFs-based hybrid HER electrocatalysts and even outperform commercial Pt/C at high current density (250 mV at 150 mA cm −2 ). The strong coupling effect of the constructed interfaces in this hybrid resulted in an efficient electron transfer from Ni2 P to Ni-MOF, which promotes the adsorption of water molecules for accelerating water dissociation step, thus boosting hydrogen generation. Further, this Ni-MOF/Ni2 P@EG could be used as cathode in alkaline Zn–H2 O cell, reaching a power density of 4.1 mW cm −2 with high stability to integrate hydrogen production with electricity generation. Graphical abstract: A strongly interface coupled Ni-MOF/Ni2 P hybrid nanoarrays is developed for highly efficient alkaline hydrogen evolution reaction and Zn–H2 O cell. Image 1 Highlights: A Ni-MOF/Ni2 P@EG hybrid nanoarray with strong coupling effect is synthesized. The Ni-MOF/Ni2 P@EG shows high activity for alkaline HER and Zn–H2 O cell. The coupling interface between Ni-MOF and Ni2 P can trigger electron transfer. The increasing Ni valence can accelerate water dissociation step in alkaline HER.